Obscuring and Feeding Supermassive Black Holes with Evolving Nuclear Star Clusters - Schartmann, M.; Burkert, A.; Krause, M.; Camenzind, M.; Meisenheimer, K.; Davies, R. I. (Proceedings of the International Astronomical Union, 2009)
Recently, high-resolution observations made with the help of the near-infrared adaptive optics integral field spectrograph SINFONI at the VLT proved the existence of massive and young nuclear star clusters in the centers of a sample of Seyfert galaxies. With the help of high-resolution hydrodynamical simulations with the pluto code, we follow the evolution of such clusters, especially focusing on mass and energy feedback from young stars. This leads to a filamentary inflow of gas on large scales (tens of parsecs), whereas a turbulent and very dense disk builds up on the parsec scale. Here we concentrate on the long-term evolution of the nuclear disk in NGC 1068 with the help of an effective viscous disk model, using the mass input from the large-scale simulations and accounting for star formation in the disk. This two-stage modeling enables us to connect the tens-of-parsecs scale region (observable with SINFONI) with the parsec-scale environment (MIDI observations). At the current age of the nuclear star cluster, our simulations predict disk sizes of the order 0.8 to 0.9 pc, gas masses of order 106M⊙, and mass transfer rates through the inner boundary of order 0.025 M⊙yr−1, in good agreement with values derived from observations.